DAMINOZIDE APPLICATION METHOD EFFECT ON GROWTH AND CONTENTS OF OLEANDRIN AND RUTIN OF OLEANDER (NERIUM OLEANDER L.) - Zyad Al-Fathul; Mohamed Al-Nijady; Taha Ahmed; Ali Qasim (Scientific Journal of Flowers and Ornamental Plants, 2017)
This study included one factor with four growth retardant application methods of daminozide at 500 mg.l-1 concentration (without addition, sapling base soaking, drench, and spraying methods) on oleander sapling four months age. The experiment was conducted in a lath-house, Department of Horticulture and Landscaping, College of Agriculture, Tikrit University, during the growing season of 2016. The experiment was designed in a complete randomized design with three replications. The results showed that daminozide applications caused a significant effect in growth characteristics. Drench application gave less plant height 62.87 cm. Spray application resulted in the highest chlorophyll content (10.61 mg.g-1 fresh weight). Highest content of oleandrin was 0.25 mg.g-1 and 47.82 mg.kg-1 of rutin to sapling base soaking treatment.